A new precipitation technique provides evidence for the permeability of Casparian bands to ions in young roots of corn (Zea mays L.) and rice (Oryza sativa L.) - Ranathunge, Kosala; Steudle, Ernst; Lafitte, Renee (Wiley, 2005)
Using an insoluble inorganic salt precipitation technique, the permeability of cell walls and especially of endodermal Casparian bands (CBs) for ions was tested in young roots of corn (Zea mays) and rice (Oryza sativa). The test was based on suction of either 100 µm CuSO4 or 200 µm K4[Fe(CN)6] into the root from its medium using a pump (excised roots) or transpirational stream (intact seedlings), and subsequent perfusion of xylem of those root segments with the opposite salt component, which resulted in precipitation of insoluble brown crystals of copper ferrocyanide. Under suction, Cu2+ could cross the endodermis apoplastically in both plant species (although at low rates) developing brown salt precipitates in cell walls of early metaxylem and in the region between CBs and functioning metaxylem vessels. Hence, at least Cu2+ did cross the endodermis dragged along with the water. The results suggested that CBs were not perfect barriers to apoplastic ion fluxes. In contrast, ferrocyanide ions failed to cross the mature endodermis of both corn and rice at detectable amounts. The concentration limit of apoplastic copper was 0.8 µm at a perfusion with 200 µm K4[Fe(CN)6]. Asymmetric development of precipitates suggested that the cation, Cu2+, moved faster than the anion, [Fe(CN)6]4–, through cell walls including CBs. Using Chara cell wall preparations (‘ghosts’) as a model system, it was observed that, different from Cu2+, ferrocyanide ions remained inside wall‐tubes suggesting a substantially lower permeability of the latter which agreed with the finding of an asymmetric development of precipitates. In both corn and rice roots, there was a significant apoplastic flux of ions in regions where laterals penetrated the endodermis. Overall, the results show that the permeability of CBs to ions is not zero. CBs do not represent a perfect barrier for ions, as is usually thought. The permeability of CBs may vary depending on growth conditions which are known to affect the intensity of formation of bands.